THE DAILY PERFORMANCE OF THE ARCHPRIEST IN THE SERRO DO FRIO COUNTY, MINAS GERAIS, 1714-1821 - Briskievicz, Danilo Arnaldo (Revista de Historia Social y de las Mentalidades, 2020)
The role of the vicar of the stick in the daily life of the social relations of the Serro do Frio District, in the Captaincy of Minas Gerais, is analyzed. The mechanisms of action of the vicar of the rod are demonstrated from the Rules of the Auditorium (1704), originated by the formal complaint of a claimant, the preparation of the parts of the process with eight witnesses and the referral to the vicar general and to the diocesan. The research methodology is bibliographic and documentary research in Brazil and Portugal. The result of the research appears in the narrative stages; we explained the work of the vicar of the stick in a chronological way, demonstrating how this figure structured around him the moralizing power of the Catholic Church.